2018
DOI: 10.1093/jamia/ocy125
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to improve engagement of hospitalized patients with their patient portals

Abstract: Objectives To test a patient-centered, tablet-based bedside educational intervention in the hospital and to evaluate the efficacy of this intervention to increase patient engagement with their patient portals during hospitalization and after discharge. Materials and Methods We conducted a randomized controlled trial of adult patients admitted to the hospitalist service in one large, academic medical center. All participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
0
17
0
9
Order By: Relevance
“…The results from a study by Anshari et al showed that the availability of a Web-based health educator is important to improving the health literacy of patients and empowering patients to control their own health and health information [37]. Greysen et al conducted a randomized controlled trial where patients in the intervention arm received tailored, structured education regarding the use of a patient portal at the bedside [38]. Study results suggested that bedside portal training produced a trend of increased ability to log in and navigate the portal, satisfaction with portal use, and frequency of portal use after discharge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from a study by Anshari et al showed that the availability of a Web-based health educator is important to improving the health literacy of patients and empowering patients to control their own health and health information [37]. Greysen et al conducted a randomized controlled trial where patients in the intervention arm received tailored, structured education regarding the use of a patient portal at the bedside [38]. Study results suggested that bedside portal training produced a trend of increased ability to log in and navigate the portal, satisfaction with portal use, and frequency of portal use after discharge.…”
Section: Resultsmentioning
confidence: 99%
“…The review by Manafo et al documented outcomes when engaging patients in health research that include the following: (1) patients feeling empowered, (2) improved trust between researcher and patients, and (3) decreased attrition of study participants. Increased engagement has also positively impacted health IT projects in different ways such as increased usage of health IT, satisfaction with health IT use [35,37,38], and the obtainment of quality/safety-related outcomes [17]. A review on patient involvement in health research by Shippee et al concluded that available literature on patient involvement focused on 1 research phase and particularly earlier stages of research.…”
Section: Discussionmentioning
confidence: 99%
“…The use of iPads to improve delivery of educational material is not a new concept. Specifically, iPads have been useful in the health care setting as a mode of delivering patient education, including education on anticoagulant medication to hospitalized patients, educational materials for patients in acute care, and improvement of inpatients' engagement in their care and patient education in the hospital [21][22][23]. Many of these previous studies have shown an improvement in patients' engagement in their care and education with the use of tablets such as iPads [24,25].…”
Section: Xsl • Fomentioning
confidence: 99%
“…9,12,[15][16][17][18] In recent years, health care systems have been trying to engage patients by offering online access to their health records via patient portals, and reported experiences regarding implementation of patient portals for acute care are now starting to emerge. 15,[19][20][21][22][23][24][25][26][27] Still, few studies have demonstrated meaningful impact on key outcomes, 20,[28][29][30] and to our knowledge, none have demonstrated the potential for using patient portals to improve concordance about the care plan, including recovery goals, among patients and clinicians in the acute care setting. 23,31,32 Improving patient-clinician communication through the meaningful use of patient portals represents a promising strategy to enhance mutual understanding about the plan and facilitate goal-concordant care for seriously ill patients during hospitalization and the transition back to the ambulatory setting.…”
Section: Background and Significancementioning
confidence: 99%